A organicidade do movimento terra livre em Goiás: espacialização e territorialização entre 2008 e 2017 - Araújo, Flávio Marcos Gonçalves de (2020)
The aim of this research was to comprehend the processes of espacialization and territorialization of the Movimento Social Terra Livre [Free Land Social Movement] between 2008 and 2017 in Goiás. Thus, it was necessary to analyze the maturation and creation of the movement, and to set up a dialogue between its concepts, social classes and territory. Another key element to comprehend the Movimento Social Terra Livre was the criticism it makes to the process of implementation of the public policies of land reform and the program Minha Casa Minha Vida [My House, My Life]. Through a literature review of the primary sources, that is, the documents of social movements, including Terra Livre, this work followed its espacialization and territorialization in Goiás. It also collected data from secondary sources such as newspapers, papers, monographs, dissertations, thesis, and the revisited archives of the Comissão Pastoral da Terra (CPT) [Pastoral Land Comission] and other government agencies as the Instituto Nacional de Colonização e Reforma Agrária (INCRA) [National Institute for Colonization and Agrarian Reform], and the extincts Ministério do Desenvolvimento Agrário (MDA) [Ministry of Agrarian Development] and Ministério das Cidades (MC) [Ministry of Cities]. After examining the sources, it was possible to chart the quantitative data and represent them in tables and maps. The qualitative data were disposed through the text. The research concluded that Terra Livre is a social movement with a strong class vision that seeks to build territories. Between 2008 and 2012, Terra Livre was the movement that realized most occupations in Goiás, so that its specialization and territorialization reached 20 counties, especially in the southwest part of the estate.